2016
DOI: 10.1097/cej.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection by anatomical site among Greek men and women: a systematic review

Abstract: Objectives We systematically reviewed the literature on anal, penile, cervical, and oropharyngeal HPV infection in Greece to provide a comprehensive overview of HPV prevalence and to explore the reporting of HPV in Greek men and women. Methods A total of 5 databases, including PubMed and Scopus, were searched up until January 1st, 2015 for studies looking at HPV prevalence, incidence, or risk factors by anatomical site. Results We identified 50 eligible studies for inclusion. The majority of them were cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
1
10
0
2
Order By: Relevance
“…Currently no data are available on HPV vaccination rates in men in Greece. The few cross-sectional studies on special male population groups studying the prevalence of sexually transmitted diseases (such as HIV positives, Men who have Sex with Men, partners of women with HPV lesions) have reported HPV prevalence 54.6%–78.4% for anal and 20.3–66.7% for penile cancers (most common HPV types, 6, 11, 16 and 18) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently no data are available on HPV vaccination rates in men in Greece. The few cross-sectional studies on special male population groups studying the prevalence of sexually transmitted diseases (such as HIV positives, Men who have Sex with Men, partners of women with HPV lesions) have reported HPV prevalence 54.6%–78.4% for anal and 20.3–66.7% for penile cancers (most common HPV types, 6, 11, 16 and 18) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 294 male patients included in this study, nearly half (49%) had an infection at a least one of the sites examined, with anal samples having the highest prevalence of HPV (33%). Previous studies conducted in Greece investigating male anal HPV prevalence have only looked at patients with a history of anal warts or anal carcinoma, and found HPV prevalence rates greater than 50% (Tsikis et al, 2015). The difference seen in our results could be due to the study population, as our study included asymptomatic but high risk men.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of HPV in Greek men is not well known as most Greek studies have focused on cervical HPV infection in women. A systematic review published by our group found that out of 50 studies on HPV prevalence and epidemiology in Greece, 20 studies have included a male population(Tsikis et al, 2015). However, the majority of these examined HPV frequency in oral and oropharyngeal cancer biopsies (n=13) while the remaining looked at HPV prevalence at anal and/or penile sites in symptomatic men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data on Greek women suggest that infection rates may be up to 43% in certain populations. 4 Fortunately, many HPV infections and HPV-related cancers can be prevented through vaccination. Originally licensed for women, HPV vaccine recommendations have since been expanded in some countries to include boys ages 11-12, as well as catch up vaccination for young men.…”
Section: Introductionmentioning
confidence: 99%